2018
DOI: 10.3390/molecules23081984
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Antibacterial Cell-Free Supernatant from Oral Care Probiotic Weissella cibaria, CMU

Abstract: Recently, studies have explored the use of probiotics like the Weissella cibaria strain, CMU (oraCMU), for use as preventive dental medicine instead of chemical oral care methods. The present study was conducted to investigate the antibacterial properties of the cell-free supernatant (CFS) from this bacterium. Cell morphology using the scanning electron microscope, and the antibacterial effect of CFS under various growth conditions were evaluated. The production of hydrogen peroxide, organic acids, fatty acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 42 publications
1
31
0
2
Order By: Relevance
“…This strain is known to inhibit caries by converting the insoluble glucan of S. mutans, a caries-inducing bacterium, into water-soluble dextran [14]. Furthermore, this strain has been reported to exhibit in vitro antimicrobial activity against Aggregatibacter actinomycetemcomitans, F. nucleatum, Porphyromonas gingivalis, Tannerella forsythia, and Treponema denticola [17]. In addition, the W. cibaria strains have been reported to be advantageous due to their competitive attachment to oral epithelial cells with periodontal pathogens in the oral cavity [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This strain is known to inhibit caries by converting the insoluble glucan of S. mutans, a caries-inducing bacterium, into water-soluble dextran [14]. Furthermore, this strain has been reported to exhibit in vitro antimicrobial activity against Aggregatibacter actinomycetemcomitans, F. nucleatum, Porphyromonas gingivalis, Tannerella forsythia, and Treponema denticola [17]. In addition, the W. cibaria strains have been reported to be advantageous due to their competitive attachment to oral epithelial cells with periodontal pathogens in the oral cavity [16].…”
Section: Discussionmentioning
confidence: 99%
“…W. cibaria CMU has been reported to inhibit the production of interleukin (IL)-6 and IL-8, which are pro-inflammatory cytokines induced by periodontal bacteria such as Fusobacterium nucleatum in oral epithelial cells [16]. Hydrogen peroxide and organic acids (e.g., lactic acid, acetic acid, and citric acid) from W. cibaria CMU have been known to be involved in antimicrobial activity [17].…”
Section: Introductionmentioning
confidence: 99%
“…[ 49 , 50 ], used the CFS of Bacillus species to inhibit the growth of bacterial pathogens. [ 51 ], reported the antimicrobial activities of various antimicrobial compounds which include lactic acid, acetic acid and H 2 O 2 in the CSF of Weissella cibaria against malodor inducing bacteria like Fusobacterium nucleatum, Porphyromonas gingivalis and Prevotella intermedia .…”
Section: Discussionmentioning
confidence: 99%
“…Considering W. cibaria a relatively recent member of LAB, the occurrence of potential probiotic strains belonging to this species still needs to be explored. Indeed, some specific W. cibaria strains had shown some beneficial effects, demonstrating antioxidant (Ye et al, 2018;Zhu et al, 2018), antimicrobial (Lim et al, 2018), anticancer (Kwak et al, 2018), and immunomodulatory features (Lee et al, 2018;Singh et al, 2018). Singh et al (2018) indicated that W. cibaria 28, a strain isolated from human infant feces, can prevent pro-inflammatory stress in Caco-2 cells challenged with LPS.…”
Section: Introductionmentioning
confidence: 99%